Achieving net zero CO2 emission in the biobased production of reduced platform chemicals using defined co-feeding of methanol - Arevalo Villa, Carlos; Marienhagen, Jan; Noack, Stephan; Wahl, Sebastian Aljoscha (Current Opinion in Biotechnology, 2023)
Next-generation bioprocesses of a future bio-based economy will rely on a flexible mix of readily available feedstocks. Renewable energy can be used to generate sustainable CO2-derived substrates. Metabolic engineering already enables the functional implementation of different pathways for the assimilation of C1 substrates in various microorganisms. In addition to feedstocks, the benchmark for all future bioprocesses will be sustainability, including the avoidance of CO2 emissions. Here we review recent advances in the utilization of C1-compounds from different perspectives, considering both strain and bioprocess engineering technologies. In particular, we evaluate methanol as a co-feed for enabling the CO2 emission-free production of acetyl-CoA-derived compounds. The possible metabolic strategies are analyzed using stoichiometric modeling combined with thermodynamic analysis and prospects for industrial-scale implementation are discussed.
CRIS-Team Scopus Importer:2023-08-11